2016
DOI: 10.21475/ajcs.2016.10.05.p7148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of planting density on vegetative growth and production components of jatropha (Physic nut L)

Abstract: Planting configuration is a management factor that influences production. Despite its importance for the establishment of commercial plantations of jatropha, the best planting configuration is still unknown, since its optimal planting density varies widely according to the climate and soil conditions of each region. This study aimed to determine the best planting configuration for jatropha cultivated in the Agreste region of Paraíba, Brazil. An experiment was set up in a randomized block design with 4 replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In this sense, tree growth is supported by the trunk and must be biomechanically balanced (Montagu et al, 2005); in other words, stem diameter is related to the length and distribution of branches and should prevent uprooting or branch split. In J. curcas, stem diameter and number of branches (Laviola et al, 2012) as well as plant height (Laviola et al, 2012;Shabanimofrad et al, 2013;De Lima et al, 2016) were shown to correlate positively with seed yield per plant.…”
Section: Multiple Regression Models For Prediction Of Plant Height Anmentioning
confidence: 95%
See 1 more Smart Citation
“…In this sense, tree growth is supported by the trunk and must be biomechanically balanced (Montagu et al, 2005); in other words, stem diameter is related to the length and distribution of branches and should prevent uprooting or branch split. In J. curcas, stem diameter and number of branches (Laviola et al, 2012) as well as plant height (Laviola et al, 2012;Shabanimofrad et al, 2013;De Lima et al, 2016) were shown to correlate positively with seed yield per plant.…”
Section: Multiple Regression Models For Prediction Of Plant Height Anmentioning
confidence: 95%
“…This increases the number of fruits per plant, facilitates control of pests and weeds, and provides easy harvesting by gaining access to all sectors of the crop canopy. According to de Lima et al (2016), J. curcas tends to increase height at high sowing densities due to interspecific competition, a condition that accelerates plant development and fruit production in this species. The same authors obtain the minimum seed yield per plant at the highest sowing density (2,500 plants ha -1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although increasing plant density by decreasing plant spacing may increase Jatropha yield per planted area, increased competition between plants may harm growth and yield (Andrianirina et al 2019;Lima et al 2016). The density of the plant population signi cantly impacted the growth and development of Jatropha, affecting both its vegetative and reproductive aspects.…”
Section: Relationships Between Yield and Growth Traits Of Jatropha Hy...mentioning
confidence: 99%
“…Previous research has recommended planting Jatropha with fairly wide spacing, such as 3 × 3 m to 4 × 4 m, as suggested by Singh et al (2013) and Huse et al ( 2011). Jatropha breeding has resulted in new genotypes with smaller canopies, which means that many areas of Jatropha cultivation can now use narrower plant spacing of 2 × 2 m or 2 × 1.5 m (Santos et al 2016;Lima et al 2016;Tar et al 2011). Narrow spacing with smaller canopies of Jatropha was achieved from a crossing between J. curcas and J. integerrima, resulting in hybrids (Arunyanark et al 2023a;Muakrong et al 2014b;One et al 2014a).…”
mentioning
confidence: 99%
See 1 more Smart Citation